Audit of the Tasmanian Transport‐Related Physical Activity Policy Environment—Lessons for Comprehensive Policy Making - M. J. Sharman; M. Mclaughlin; P. McCue; T. Washington; V. J. Cleland (Health Promotion Journal of Australia, 2026)
ABSTRACT Issue Addressed Government policy largely determines the transport‐related physical activity (TRPA) environment—an environment central to global PA promotion frameworks (e.g., Global Action Plan on Physical Activity). However, little is known about this policy environment—a knowledge gap this study aimed to fill in Tasmania. Methods Guided by the Comprehensive Analysis of Policy on Physical Activity (CAPPA) framework, the World Health Organisation's Health Enhancing Physical Activity Policy Audit Tool (PAT) Version 2 was contextualised to reflect the study's subnational and TRPA focus (PAT‐C). In 2024, a five‐person Tasmanian multi‐sector project team completed the PAT‐C. The audit included 20 policy documents systematically extracted from Tasmanian government websites screened for TRPA relevance. After PAT‐C completion, a SWOT analysis underpinned by the CAPPA identified strengths, weaknesses, opportunities and threats of the TRPA policy environment. Results Key strengths were: 9/20 policy documents directly supported TRPA; many agencies/formal groups/mechanisms within/outside of subnational government provide TRPA leadership/advocacy. Main weaknesses were: 11/20 policy documents made no/indirect TRPA reference; certain settings and population groups for TRPA targeting were overlooked across policies; disclosure of consultation and policy cross‐referencing was inconsistent; missing were mechanisms to ensure evidence‐based policy, a TRPA communication strategy, dedicated funding, specific targets, robust measures and comprehensive TRPA intervention evaluation. Targeted advocacy addressing TRPA‐related policy environment omissions was a key opportunity. Fluctuating political commitment and operating environments were important threats. Conclusion and So what: Many gaps in the TRPA environment were identified that, if filled, could support population‐level health gain by tackling upstream influences on physical activity.